2018
DOI: 10.15407/ubj90.04.025
|View full text |Cite
|
Sign up to set email alerts
|

The Р60-S6K1 isoform of ribosomal protein S6 kinase 1 is a product of alternative mRNA translation

Abstract: Ribosomal protein S6 kinase 1 (S6K1) is a well-known downstream effector of mTORC1 (mechanistic target of rapamycin complex 1) participating primarily in the regulationA number of downstream effects of mTORC1, including protein biosynthesis, cell growth, proliferation and survival [4,5] are mediated via ribosomal protein S6 kinase 1 (S6K1), a well-studied mTORC1 substrate.The S6K1 gene (RPS6KB1) was shown to encode two well-known S6K1 isoforms, p85-S6K1 and p70-S6K1, that differ only by the presence of the Nte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…We recently reported that HEK-293 cells expressing only the p60 isoform (p85 -/p70 -/ p60 + HEK-293 cells) display higher rates of cell proliferation and cell migration compared to HEK-293 with knockout of all isoforms [6]. These observations suggest that p60-S6K1 could be involved in the control of cell proliferation and motility.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We recently reported that HEK-293 cells expressing only the p60 isoform (p85 -/p70 -/ p60 + HEK-293 cells) display higher rates of cell proliferation and cell migration compared to HEK-293 with knockout of all isoforms [6]. These observations suggest that p60-S6K1 could be involved in the control of cell proliferation and motility.…”
Section: Resultsmentioning
confidence: 98%
“…HEK-293 and p85 -/p70 -/p60 + HEK-293 cells were maintained in Dulbecco's Modified Eagle's Medium (DMEM) (GIBCO) containing 10% fetal bovine serum (FBS) (GIBCO), 100 units/ml penicillin, and 100 µg/ml streptomycin. Development of cell clones modified with CRISPR/Cas9 targeting p85-and p70-S6K1 was described in [6]. For experiments involving serum stimulation, rapamycin and LY294002 inhibition, cells were washed twice with phosphatebuffered saline (PBS) and after that serum-starved for 24 h in DMEM deprived of serum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations